Effect of Acid Base Source on Physical Properties in Effervescent Granule Formulation : A Review - Pratama, Reza; Hasanah, Ida; Nurasih, Widya; Sagita, Novaliana Devianti (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Background: Indonesia has abundant natural resources, including types of herbal plants. Herbal plants in Indonesia have various health benefits and have been widely processed in the form of functional drinks. Aim:. To reduce the often undesirable taste and odor characteristics of herbal medicine, it can be further processed into derivative products that taste good and have a longer shelf life. One way is to process it into an effervescent preparation. Method: Searching and collecting journal information is carried out electronically, namely by accessing international and national journal search sites such as online from Pubmed, Google Scholar and Sciencedirect. by using the keywords "Effervescent Granules" and "Effervescent Herbal Drinks". Result: In effervescent granules there are acids and bases, the acids used are citric acid and tartaric acid which are acid components commonly used in effervescent granules. The use of a single acid will cause difficulties in its manufacture. The combination of citric acid and tartaric acid in effervescent granule preparations aims to simplify the process of making effervescent granule formulations. Conclusion: The results of existing literature studies show that the combination of acids in effervescent preparations greatly facilitates the process of forming effervescent granules. The use of different combinations of acid sources affects the physical properties of effervescent granules, including flow rate, dissolution time, pH and others. Sodium bicarbonate as a base source has the most significant influence on water content. The acid combination commonly used in making effervescent granules is citric acid and tartaric acid. Keywords: Effervescent granules, citric acid, tartaric acid, sodium bicarbonate